A forward phenotypically driven unbiased genetic analysis of host genes that moderate herpes simplex virus virulence and stromal keratitis in mice. - Richard L Thompson; Robert W Williams; Malak Kotb; Nancy M Sawtell (PLoS ONE, 2014)
Both viral and host genetics affect the outcome of herpes simplex virus type 1 (HSV-1) infection in humans and experimental models. Little is known about specific host gene variants and molecular networks that influence herpetic disease progression, severity, and episodic reactivation. To identify such host gene variants we have initiated a forward genetic analysis using the expanded family of BXD strains, all derived from crosses between C57BL/6J and DBA/2J strains of mice. One parent is highly resistant and one highly susceptible to HSV-1. Both strains have also been fully sequenced, greatly facilitating the search for genetic modifiers that contribute to differences in HSV-1 infection. We monitored diverse disease phenotypes following infection with HSV-1 strain 17syn+ including percent mortality (herpes simplex encephalitis, HSE), body weight loss, severity of herpetic stromal keratitis (HSK), spleen weight, serum neutralizing antibody titers, and viral titers in tear films in BXD strains. A significant quantitative trait locus (QTL) on chromosome (Chr) 16 was found to associate with both percent mortality and HSK severity. Importantly, this QTL maps close to a human QTL and the gene proposed to be associated with the frequency of recurrent herpetic labialis (cold sores). This suggests that a single host locus may influence these seemingly diverse HSV-1 pathogenic phenotypes by as yet unknown mechanisms. Additional suggestive QTLs for percent mortality were identified--one on Chr X that is epistatically associated with that on Chr 16. As would be anticipated the Chr 16 QTL also modulated weight loss, reaching significance in females. A second significant QTL for maximum weight loss in male and female mice was mapped to Chr 12. To our knowledge this is the first report of a host genetic locus that modulates the severity of both herpetic disease in the nervous system and herpetic stromal keratitis.